Kreativitas Guru Pendidikan Agama Islam dalam Mengatasi Kejenuhan Siswa Belajar Al-Qur’an Hadis di MTsN I Pasaman - Ayani, Misda; Husni, Arman; Kamal, Muhiddinur; Junaidi, Junaidi (Darul Yasin Al Sys, 2023)
The reason the author raised this problem as a scientific work in the form of a thesis is because the author found that in the process of learning Al-Qur'an hadith subjects students often get bored with learning. This is caused by the lack of creativity of Islamic Religious Education teachers in developing their creativity. The use of learning methods and media by Islamic Religious Education teachers are the obstacles or barriers that teachers face in developing their creativity. The problem that the author examines is how the creativity of Islamic religious education teachers overcomes the boredom of students studying Al-Qur'an Hadith at MTsN I Pasaman, and the causes of students' boredom studying Al-Qur'an Hadith at MTsN I Pasaman. And this research aims to determine the creativity of Islamic Religious Education teachers in overcoming the boredom of students studying Al-Qur'an Hadith at MTsN I Pasaman, and to find out the causes of student boredom studying Al-Qur'an Hadith at MTsN I Pasaman. This research is a qualitative descriptive research. The subjects in this research were Al-Qur'an Hadith teachers and students in class VIII 6. This research used three data collection techniques, namely: observation, interviews, and documentation. This research used two informants, namely key informants and supporting informants. The validity of the data in this research uses source triangulation, data triangulation, and time triangulation Based on the results of research carried out, the author found that what causes boredom in students learning Al-Qur'an Hadith is due to the lack of variety in the use of media and learning methods by teachers. Meanwhile, in terms of teacher creativity education religion islam at MTsN I Pasaman it cannot be said to be creative in using and varying learning media in learning Al-Qur'an Hadith, and its implementation or translation is still not good. The teacher's creativity in varying methods and media is only in the learning design stated in the RPP, due to inadequate time conditions. The lack of application of the use of media and methods causes students' boredom in learning Al-Qur'an Hadith to not be resolved properly by teachers.